تحليل واقع وأثر التجارة الإجتماعية في سلوك المستهلك الشرائي دراسة استطلاعية في قسم إدارة الأعمال/ جامعة نوروز - حسين, احسان محسن (Sulaimani Journal for Humanities, 2021)
The a ccelerating and in creased development in the techniques and tools used in Marketing in the recent century specially the international directions of information technology(IT) applications in digital marketing create a substantial need to pursue these improvement. This study aims to shed light on one of these tools which is social commerce and its effect on customers Purchasing behavior. Accordingly, the study’s importance lay in the excretion of the important role of social commerce among customers and organizations in need to pursue any new. In order to best solve study’s problem, a questionnaire has generated and spread over a sample of (100) second, third, and fourth grade students in business management department that represent studies population. The most important result extracted from the study is that social commerce consider to be the most effective tool of products and services marketing and the proper direction for this era. While the basic suggestion in the study articulates in the preferences of using social commerce platforms as an effective marketing tool by Kurdistan region of (KRG) organization.
Keywords: Social Commerce; Customers Behavior; Social Network; Social Media